2014
DOI: 10.1038/ejcn.2014.99
|View full text |Cite
|
Sign up to set email alerts
|

Associations between 25-hydroxyvitamin D levels and pregnancy outcomes: a prospective observational study in southern China

Abstract: The prevalence of low level of vitamin D (serum 25OHD ⩽20 ng/ml) was 18.9% among pregnant women in southern China. There were no significant differences in most adverse pregnancy outcomes among pregnant women with different levels of vitamin D at 16-20-week gestation except for higher prevalence of gestational diabetes and preterm delivery in women with high level of vitamin D, possibly related to the older age and higher body mass index of this group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
149
6
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(178 citation statements)
references
References 31 publications
13
149
6
3
Order By: Relevance
“…[3536] Zhou et al . [37] examined the effect of vitamin D on pregnancy outcomes, and their results showed that at the end of pregnancy, macrosome neonate, rate of C/S, birth weight, and congenital abnormalities were observed, consistent with our study's results; however, no decrease was observed in the Apgar score, while the prevalence of gestational diabetes and preterm delivery was higher in the group who had received higher levels of vitamin D than in women who had received low or moderate levels of vitamin D.[3738]…”
Section: Discussionsupporting
confidence: 89%
“…[3536] Zhou et al . [37] examined the effect of vitamin D on pregnancy outcomes, and their results showed that at the end of pregnancy, macrosome neonate, rate of C/S, birth weight, and congenital abnormalities were observed, consistent with our study's results; however, no decrease was observed in the Apgar score, while the prevalence of gestational diabetes and preterm delivery was higher in the group who had received higher levels of vitamin D than in women who had received low or moderate levels of vitamin D.[3738]…”
Section: Discussionsupporting
confidence: 89%
“…The score for one article, however, was unable to be evaluated because the full text was not available, and three RCT had low risk of bias. Table 1 lists the characteristics of the 18 observational studies 9,[12][13][14][15][16][17][18][19][20][21][22][23][24][30][31][32] and six RCT. [33][34][35][36][37][38] There was some disparity in the definition of PTB between studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…Four studies [19, 20, 21, 22] were randomized controlled trials (RCTs).Two studies [23, 24] were post hoc analyses of RCT. Prospective cohort design was applied by six studies [25, 26, 2729, 30]. One study [31] was a restrospective cohort.…”
Section: Resultsmentioning
confidence: 99%